Optimal Pricing Strategy for New Products - Krishnan, Trichy V.; Bass, Frank M.; Jain, Dipak C. (Management Science, 1999)
Robinson and Lakhani (1975) initiated a long research stream in marketing when they used the Bass model (1969) to develop optimal pricing path for a new product. A careful analysis of the extant literature reveals that the research predominantly suggests that the optimal price path should be largely based on the sales growth pattern. However, in the real world we rarely find new products that have such pricing pattern. We observe either a monotonically declining pricing pattern or an increase-decrease pricing pattern that does not seem close to the sales path. In this paper, we use a variation of the generalized Bass model (called GBM) developed by Bass et al. (1994) that yields optimal pricing policies that are consistent with empirical data.